(3GdJRGeGJ GdTGMf ai YbO Gdfbd GdOhdi ddHVGFY habG dCMcGe bhGYO QhJQOGe (B2008 (3dfbd GdHVGFY OhdjG YHQ GdHMQ(B: s (3OQGSI ebGQfI (B/ s - (3GeMeO aJM Gddg GeMeO YHOGdMejOs; (3LeGd eMehO YHOGdYRjR s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3YGdLJ GdQSGdI GdJRGeGJ GdTGMf ai YbO Gdfbd GdOhdi ddHVGFY habG dCMcGe dbhGYO QhJQOGe (B2008 (3dfbd GdHVGFY OhdjG YHQ GdHMQ(B: (3HhUag WQaG PG TCf ai YbO Gdfbd h jJMed GdGdJRGeGJ GdJi JfTC Yfg hjSCd Yf GdENdGd HgG HehLH GdGJaGbjGJ GdOhdjI h GdJTQjYGJ GdeMdjI Ydi MO ShGA(B: (3h CHQR eG jKjQ GdJSGDd ai gPG GdHMK HjGf MLe GdRjGOI ai GdJRGeGJ GdTGMf habG dCMcGe bhGYO QhJQOGe ebGQfI HGdGJaGbjGJ GdOhdjI GdSGHbI (B((3bhGYO HQhcSd h bhGYO gGeHhQL(B) (3h GdJTQjYGJ GdeMdjI(B: (3h EPG cGfJ fUhU GdGJaGbjI dG JLjR (B- (3HMSH GdCUd (B- (3dWQa GdYbO GdGJaGb Ydi RjGOI GdGdJRGeGJ GdJi jJMedgG GdTGMf ai ehGLgI GdfGbd(B: (3h Cf gPG GdMce jhaQ bOQG CcHQ ef GdMeGjI de jcf jMX Hg GdTGMf ai Xd GdGJaGbjGJ GdOhdjI GdSGHbI(B: (3ZjQ Cf GdJSGDd Yf eOi RjGOI MLe GdJRGeGJ GdTGMf HehLH bhGYO QhJQOGe jXd bGFeG MJi eY hLhO gPG GdMce(B. (3h bO GJHY ai EYOGO gPG GdHMK WQjbI GdhUa GdJMdjdi GdfbOi h GdebGQf(B: (3h GdPi jYJeO Ydi JMdjd fUhU GdGJaGbjI GdeJYdbI HGdJRGeGJ GdTGMf ai YbO Gdfbd GdOhdi ddHVGFY YHQ GdHMQ habG dCMcGe bhGYO QhJQOGe(B: (3h ebGQfJgG HGdGJaGbjGJ GdOhdjI GdSGHbI GdJi oYfjJ HJfXje YbO Gdfbd GdOhdi ddHVGFY YHQ GdHMQ(B: (3h GdJTQjYGJ GdeMdjI GdefXeI ddfbd GdHMQi ai GdOhd GdeJWhQI cGdhdGjGJ GdeJMOI GdCeQjcjI h GdeedcI GdeJMOI GdHQjWGfjI h bGfhf GdJLGQI GdHMQi GdeUQi GdMGdi(B. (3h jfUH Ld GdJQcjR Ydi eG JbOeg GdJTQjYGJ eMd GdHMK ef Mdhd deG bO jYJQi GdYdGbI Hjf CWQGa YbO Gdfbd ef NdGaGJ JJYdb HeG jaJQV Cf jdJRe Hg GdTGMf ef hGLHGJ ai ehGLgI GdfGbd h GdeSDhdjI GdJi JfTC Yf GdENdGd HgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2020s
(3HHdjhLQGajG(B: (3UaMGJ (B292-303s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdJRGeGJ GdTGMfs; (3bhGYO QhJQOGes; (3GdJRGeGJ GdTGMf aj YbO Gdfbd GdHMQjs; (3GdGdJRGe HJgjFI GdHVGYI ddfbds; (3GdJRGeGJ GdTGMf GdeJYdbI Hfbd GdehGO GdNWQIs; (3GdGdJRGe HOaY CLQI Gdfbd s; (3GdJRGeGJ GdTGMf GdebQQI HGdGJaGb eY GdfGbds; (3eSFhdjI GdTGMf GdYbOjIs; (3eSFhdjI GdTGMf GdJbUjQjIs; (3OYhi eSFhdjI GdTGMf s; (3JShjI efGRYGJ GdJLGQI GdHMQjI Yf WQjb GdJMcjes; (3GJaGb GdJMcje aj bhGYO QhJQOGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs